Case report: Pulmonary artery sarcoma diagnosed through rare brain metastases - Tan, Na; Ouyang, Zhiqiang; Duan, Xirui; Zhou, Xinyan; Zhu, Yu; Chu, Jixiang; Luo, Dan; Dai, Hai-Long; Liao, Chengde (Frontiers in Oncology, 2024)
We present the case of a 33-year-old male referred across several hospitals because of suspected chronic thromboembolic pulmonary hypertension (CTEPH). Initially admitted in October 2022 for a recurrent, severe cough and diagnosed with CTEPH, he received anticoagulant therapy. However, his symptoms worsened, necessitating a transfer to another facility for thrombolysis treatment. Following an episode of syncope, an MRI scan revealed a metastatic brain tumor. Subsequently, he experienced a third transfer to our hospital, emergency surgery was performed to alleviate cerebral edema and excise a lesion in the left frontal lobe. Postoperative pathology was inconclusive, but a multidisciplinary team meeting, aided by experienced radiologists, eventually confirmed a diagnosis of pulmonary artery sarcoma (PAS) with systemic metastases. This case underscores the necessity of promptly ruling out PAS in patients presenting with significant emboli in the central pulmonary arteries and suggests early referral to specialized centers for suspected cases.In the recent revision process, Zhiqiang Ouyang has demonstrated high professionalism and taken on extra workload. He polished the English grammar and wording of the article, introduced new discussion points, and improved the structure and clarity of the arguments, making the content more comprehensive and persuasive. These contributions have significantly enhanced the quality and impact of the paper. Therefore, I believe it is appropriate to adjust the order of authors to list Zhiqiang Ouyang as a co-first author, a request that has also been confirmed by the corresponding author, Chengde Liao . Furthermore, literature reports indicate that brain metastases , although rare (3), generally emerge postsurgically, underscoring the complex management required for this condition and suggesting a potential for poorer outcomes. This case report details the diagnostic journey of a young male with suspected pulmonary artery intimal sarcoma, characterized by extensive systemic metastases and numerous hospital referrals before confirmation of his condition.